Semiochemicals produced by fungal bark beetle symbiont Endoconidiophora rufipennis and the discovery of an anti-attractant for Ips typographus - Lindmark, Matilda; Ganji, Suresh; Wallin, Erika A; Schlyter, Fredrik; Unelius, C Rikard (PLoS One, 2023)
Bark beetles vector symbiotic fungal species into their host trees during mass attacks. The symbiotic relationship with blue stain fungi of the Ascomycetes, including genera of Endoconidiophora (syn. = Ceratocystis), promotes successful establishment whereby the microbes help to overcome the host trees' defence and degrade toxic resins. This is the first study to evaluate both the volatile emissions from an insect-associated blue stain fungus over time and the insect response in a field trapping experiment. Volatile emissions from isolates of Endoconidiophora rufipennis (ER) were collected by solid-phase microextraction (SPME) and analysed by gas chromatography-mass spectroscopy (GC-MS) over a period of 30 days. This virulent North American fungus is closely related to E. polonica, a symbiotic fungus known from Eurasian spruce bark beetle Ips typographus.Nine volatiles were emitted by ER in substantial amounts: isoamyl acetate, sulcatone, 2-phenethyl acetate, geranyl acetone, geranyl acetate, citronellyl acetate, (R)- and (S)-sulcatol, and (R)-sulcatol acetate. A late peaking compound was geranyl acetone. In the field trapping experiment, three of the fungal volatiles (geranyl acetone, 2-phenethyl acetate and sulcatone) were tested in combination with a synthetic aggregation pheromone for I. typographus. Traps with geranyl acetone attracted lower numbers of I. typographus compared to traps with 2-phenethyl acetate, sulcatone or the pheromone alone as a control. The results showed that geranyl acetone acts as an anti-attractant and may act naturally on I. typographus as a cue from an associated fungus to signal an overexploited host.
Keywords: Ascomycota; Plant Bark; Animals; nosatcovití; Coleoptera; brouci; feromony; Pheromones; zvířata; Weevils; kůra rostlin